2017
DOI: 10.1080/13607863.2017.1399350
|View full text |Cite
|
Sign up to set email alerts
|

‘It is nothing more than a senior moment’: the moderating role of subjective age in the effect of change in memory on self-rated memory

Abstract: While preserving a young subjective age is usually considered an adaptive strategy, it also has potential negative effects, masking changes in memory performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
3
12
0
Order By: Relevance
“…Our results are in line with those studies reporting a statistically significant, but small association between more negative self-perceptions of cognition and poorer objective cognition (Amariglio et al, 2012). This may be due to self-perceptions of cognition being influenced by many psychosocial factors including depressive symptoms and negative ATOA (Segel-Karpas and Palgi, 2019;Siebert et al, 2020). Indeed, in our study, higher levels of AARC losses in cognition are associated with more severe depression and anxiety, more negative ATOA, an older SA, and poorer SRH.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in line with those studies reporting a statistically significant, but small association between more negative self-perceptions of cognition and poorer objective cognition (Amariglio et al, 2012). This may be due to self-perceptions of cognition being influenced by many psychosocial factors including depressive symptoms and negative ATOA (Segel-Karpas and Palgi, 2019;Siebert et al, 2020). Indeed, in our study, higher levels of AARC losses in cognition are associated with more severe depression and anxiety, more negative ATOA, an older SA, and poorer SRH.…”
Section: Discussionsupporting
confidence: 93%
“…A recent longitudinal study showed that more negative ATOA predict greater perceived cognitive decline [ 59 ]. Similarly, individuals with an older felt age perceive more age-related losses in the cognitive domain [ 60 ]. Overall, results relating to the construct validity of the AARC-10 SF and the AARC-50 cognitive functioning subscale suggest that levels of AARC losses and AARC gains are informative of individuals’ mental, physical, and cognitive health.…”
Section: Discussionmentioning
confidence: 99%
“…A recent longitudinal study showed that more negative ATOA predict greater perceived cognitive decline (Siebert, Braun, & Wahl, 2020). Similarly, individuals with an older felt age perceive more age-related losses in the cognitive domain (Segel-Karpas & Palgi, 2019).…”
Section: Validity Of the Aarc-10 Sf And Aarc-50 Cognitive Functioningmentioning
confidence: 98%